Border fascism in the Venezia Giulia - Matajc, Vanesa (Acta Histriae, 2016)
Slovenian literary texts which refer to the border Fascism, recognize its fascist discourse as colonial. They "quote" it and refer to it, they put it under the question and they deny it. A Slovenian literary character, constructed as the colonial subaltern in the fascist-Italian view, rejects this image in the name of Slovenian auto-stereotype of a revolter: the literary character rejects the very possibility of being treated as a colonized subject and thus actually confirms the border Fascism as a set of colonization strategies characteristic of the concept of proximate colony. The article is an introduction to postcolonial reading of selected Slovenian literary texts and also an introduction to the concept of proximate colony (R. Donia, S. Vervaet). Slovenian literary representations, i.e. the literary "contact zone" of two border cultures of Venezia Giulia off er a chance to reflect the border Fascism policy from the perspective of colonial relations between the imperial centre and the periphery, inhabited mostly by the disloyal non-Italian population.
Keywords: Julian March; Julijska krajina; obmejni fašizem; Pahor, Boris, 1913-; Pirjevec, Nedeljka, 1932-2003; postkolonializem; Rebula, Alojz, 1924-; Slovene literature; slovenska književnost